The Catcher in the Rye - Salinger, J. D. 1919-2010. (Jerome David) (Bronx, NY Ishi Press International, 2013)
A 16-year old American boy relates in his own words the experiences he goes through at school and after, and reveals with unusual candour the workings of his own mind. What does a boy in his teens think and feel about his teachers, parents, friends and acquaintances?
Keywords: Caulfield, Holden (Fictitious character) -- Fiction; Runaway teenagers -- Fiction; New York (N.Y.) -- Fiction; Bildungsromans